Graphene pillared with hybrid fullerene and nanotube as a novel 3D framework for hydrogen storage: A DFT and GCMC study. (10th July 2020) - Bi, Lan; Yin, Jie; Huang, Xin; Wang, Yunhui; Yang, Zhihong
Abstract: A new-type 3D pillared graphene framework with hybrid fullerene and nanotube pillars (PGF-hFN) has been created depended on density functional theory (DFT) and first-principles molecular dynamics simulations (MD). It is proved to have excellent thermal structural stability. The average adsorption energy of Li is 2.77 eV much higher than the metal cohesive energy excluding lithium aggregation problem. From DFT calculations, for Li-decorated B-doped PGF-hFN, the hydrogen gravimetric density (HGD) is as high as 12.92 wt% and the according volumetric uptake is 96.4 g/L with an average adsorption energy of 0.195 eV per H2 . Further grand canonical Monte Carlo (GCMC) simulations predict 7.2 wt% in excess HGD and 53.8 g/L in excess volumetric hydrogen density at near ambient temperature (233 K) and 100 bars with the ideal adsorption enthalpy which have exceeded the 2020 the U.S. Department of Energy (DOE) ultimate target for mobile applications. Our multiscale theoretical simulations indicate this new pillared structure should be a promising carrier accessible for sorption of hydrogen molecules. Graphical abstract: Calculated H2 adsorption isotherms by GCMC in 48Li@B-doped PGF-hFN as a function of the pressure at T = 233 K. The inset: the side view of the optimized 1 × 2 × 2 supercells of 192H2 @48Li@C200 B24 frameworks by a DFT study. Pink indicates Boron; blue, Nitrogen; gray, Carbon; white, Hydrogen; purple, Lithium. Image 1 Highlights: A pillared graphene framework with hybrid fullerene and nanotube pillars is modeled. Both Li decoration and B doping in PGF-hFN improve hydrogen adsorption. The average binding energy of adsorbed Li atoms (2.77 eV) avoids Li clustering. High hydrogen storage capacity is 12.9 wt% and 96.4 g/L calculated from DFT. Excess H2 storage capacity is 7.2 wt% and 53.8 g/L at 233 K and 100 bars from GCMC.